The laryngeal twitch response – Can it avoid unnecessary two-stage thyroidectomy? – A retrospective cohort study. (December 2019) - Gschwandtner, Elisabeth; Netz, Judith; Passler, Christian; Bobak-Wieser, Ruth; Göbl, Susanne; Tatzgern, Elisabeth; Schneider, Max; Handgriff, Laura; Hermann, Michael
Abstract: Background: The objective of this study was to determine if the laryngeal twitch response, when compared to neuromonitoring, can predict postoperative vocal cord function and can thus be used in case of technical failure of the EMG-recording electrode. Methods: A total of 640 nerves at risk were included in this study based on a prospective protocol. The laryngeal twitch response and the EMG-records were compared with the results of the postoperative laryngoscopy. Results: Of the 640 nerves at risk, 582 showed a normal postoperative vocal cord function. A recurrent laryngeal nerve paralysis (no vocal fold movement) was observed in 39 cases and recurrent laryngeal nerve paresis (reduced vocal cord movement) was diagnosed in 19 cases. The overall negative predictive value (NPV) in final vagus nerve stimulation (V2) was 95.0% for the EMG-records and 94.8% for the laryngeal twitch response. When pareses were excluded, the NPV was 96.8% and 96.6% respectively. The positive predictive value (PPV) of vagus nerve stimulation lies between 51.4% and 57.1% excluding the pareses. It rises to values between 60.0% and 65.1% if they are included. Conclusions: The laryngeal twitch response and the EMG-records show similar results, and the NPV is good in both. Thus, in case of technical failure or displacement of the EMG-recording electrode, the laryngeal twitch can be used in decision-making for or against a two-stage thyroidectomy. Highlights: Laryngeal twitch as alternative to intermittent neuromonitoring. Normal postoperative vocal cord function in 90.9% of the patients. Negative predictive value is over 93% for laryngeal twitch and intermittent neuromonitoring. High specificity for laryngeal twitch response.